ANALISA KESTABILAN LERENG DENGAN METODE JANBU MENGGUNAKAN SOFTWARE SLIDE 6.0 PADA AREA JALAN TAMBANG CV. PUTRA IDOLA, KOTA PADANG, PROVINSI SUMATERA BARAT - Muhammad Kelvin Varlen; Bamabang Heriyadi (Journals Mining Engineering : Bina Tambang, 2023)
Abstract. CV. Putra Idola is one of the companies engaged in the mining business with the type of minerals being mined is Andesite stone located in Nagari Siguntur Muda, Bungus Teluk Kabung District, Padang City, West Sumatra. The mining activity applied is an open pit mining system with the Open Mining method. On the slopes of the mine road CV. Putra Idola has 2 single slopes with the material for making the slopes is andesite stone. On single slope 1 there is a transportation road for mining operations, while on single slope 2 there is a settling pond. The slope of the research area has a slope height of 17 meters and a slope of 35o for single slope 1, and for single slope 2 it has a height of 19 meters with a slope of 32°. The overall slope is 31 meters high with a slope of 62o. On the slope walls there are many weak areas and rock layers, so that the prone slopes will be at risk of landslides, so a good calculation is needed to avoid landslides.The results of the actual slope analysis using the simple Janbu method, the safety factor (FK) on slope 1 is 1,263 when natural conditions when the slope is saturated has a safety value (FK) of 1,239. The value of safety factor (FK) on slope 2 is 1.666 under natural conditions, while when the slope is saturated it has a safety factor value (FK) of 1.625 On the slopes as a whole obtained a safety value (FK) of 1,079 when the natural condition and 1,063 when the slope is saturated. Mine slope geometry recommendations based on the results of slide 6.0 software analysis obtained the value of safety factor (FK) for slope 1 of 1.325. while in a saturated state the safety factor (FK) is 1.300 with a slope of 17 m and a slope of 68°. The overall slope geometry recommendation based on slide 6.0 software analysis obtained a safety value (FK) of 1.329. while in a saturated situation the safety yield (FK) is 1.311 with a slope of 31 m and a slope of 49°